Clinical profile of oral mucosa lesions in elderly patients: a 20-year retrospective study. - de Almeida Lança, Maria Leticia [UNESP]; Bagatini, Ana Thais [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Fernandes, Darcy [UNESP]; de Oliveira Barbeiro, Camila [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Silva, Evânio Vilela [UNESP]; Navarro, Claudia Maria [UNESP]; Silveira, Heitor [UNESP]; Bufalino, Andreia [UNESP] (Universidad del Valle, 2023)
BACKGROUND: Life expectancy has considerably increased resulting in population aging. Studies evaluating the outcomes of aging in oral health are scarce. OBJECTIVE: Evaluate retrospectively the profile of elderly patients from a public Oral Medicine Center during a period of 20 years. METHODS: A qualitative and quantitative retrospective observational study was conducted analyzing medical records from an oral medicine service from January 1994 to December 2014. Results were reported as mean ± standard deviation for quantitative variables and percentages for categorical variables. The Chi-square test and multivariate binary logistic regression were performed when necessary to a significance level of 5%. RESULTS: 2,690 medical records were retrieved, comprising of 61% women and 39% men with an average age of 68.8 ± 6.79 years. Xerostomia was significantly associated to female gender, hypoglycemic usage, antihypertensive usage, psychotropic usage, and analgesics and anti-inflammatory usage. As for candidiasis, an association with age, alcohol consumption, and use of complete dentures was found. CONCLUSION: A longer life expectancy should be accompanied by a long-term care follow-up of the population. Diseases and side effects related to the elderly are going to be more common. Therefore, dental care services should aim to prevent and treat these complications as way to improve the elderly’s quality of life.